Skogsmaskiners bränsleförbrukning - Karlsson, Petter; Sylvén, Olof (SLU/Dept. of Forest Products, 2006)
This report is a thesis work for a B.Sc. in Forestry exam at the 5028, SLU. The aim of the work was to compare fuel consumption during work in practical field conditions with a standardized method developed by Skogforsk (The Forestry Research Institute of Sweden), (Brunberg, 2005) for harvesters and forwarders from different manufacturers and of different sizes in order to promote the development of more fuel efficient machines.